Exchange and spin relaxation in solid 3He - Cowan, Brian; Fardis, Mihail (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1997)
Spin relaxation measurements in solid 3He in the temperature region where exchange dominates the behaviour are reviewed and re-analysed. A model is adopted which conflates the complex exchange modulation of the dipolar interaction into a single correlation time. This may be regarded as introducing an effective pairwise exchange Hamiltonian. Within the confines of this model new procedures are proposed for obtaining mathematical expressions for the dipolar autocorrelation function and the spectral density functions which determine the relaxation times. By the appropriate treatment of short-time and long-time asymptotic behaviour, together with a method for taking into account the mid-range behaviour, it is possible to fit the experimental data externely well. The very success of this procedure seems surprising in the light of multiple spin exchange in solid 3He. It is an indication that the dominant exchange processes all scale with density in a similar way. This is supported by path integral Monte Carlo calculations. Some consequences and implications of this are discussed.